A non-invasive biomechanical device to quantify knee rotational laxity: Verification of the device in human cadaveric specimens - Jeffrey Chun-Yin Lee; Patrick Shu-Hang Yung; Mak-Ham Lam; Aaron See-Long Hung; Daniel Tik-Pui Fong; Wood Yee Chan; Kai-Ming Chan (Elsevier, 2019)
Background: Biomechanical measurement tools have been developed and widely used to precisely quantify knee anterior-posterior laxity after anterior cruciate ligament (ACL) injury. However, validated objective device to document knee rotational laxity, though being developed by different researchers, are not yet widely used in the daily clinical practice. A new biomechanical device was developed to quantify knee internal and external rotations. Methods: The reliability of the new biomechanical device which measures knee rotations were tested. Different torques (1-10Nm) were applied by the device to internally and externally rotate human cadaveric knees, which were held in a flexion angle of 30°. The rotations were measured by the device in degrees. There were two independent testers, and each tester carried out three trials. Intra-rater and inter-rater reliability were quantified in terms of intraclass correlation (ICC) coefficient among trials and between testers. The device was verified by the comparison with a computer assisted navigation system. ICC was measured. Mean, standard deviation and 95% confident interval of the difference as well as the root mean square difference were calculated. The correlations were deemed to be reliable if the ICC was above 0.75. Results: The intra-rater and inter-rater reliability achieved high correlation for both internal and external rotation, ranged from 0.959 to 0.992. ICC between the proposed meter and the navigation system for both internal and external rotation was 0.78. The mean differences were 2.3° and 2.5° for internal and external rotation respectively. Conclusions: A new knee rotational laxity meter was proposed in this study. Its reliability was verified by showing high correlation among trials. It also showed good correlation to a gold standard of measurement. It might be used to document knee rotational laxity for various purposes, especially after ACL injury, after further validation of the device in human subjects. Keywords: Tibial rotation, Knee stability, Measurement, Laxity